Type Analysis of Speaking Performance Assessment Task in English for Nusantara Textbook - Dewantara, Kadek Andre Karisma (Universitas Pendidikan Ganesha, 2023)
One of the key factors in the success of learning English is the use of textbooks. The English textbook entitled